Consequences on neurological development in children with Lennox-Gastaut Syndrome (Research, Society and Development, 2024)
Lennox-Gastaut Syndrome (LGS) is a severe epileptic encephalopathy with onset in childhood, which accounts for 4% of childhood epilepsies. GLS does not yet have a defined etiopathogenesis and treatment, resulting in a poor prognosis for these patients. Several treatments are being studied to control convulsive episodes and to neuroprotect these patients. This review aimed to identify what the consequences would be for the neurological development of children with LGS and the treatments available through a systematic bibliographic review, of publications from 2014 to 2024, in Portuguese, English and Spanish. A survey was carried out in the PubMed and SciELO databases. There are few studies on the subject, a reality that needs to be changed so that these infants have a better quality of life. But despite this, it is concluded that although the neuropsychomotor system is still affected even when using the treatment, these children still have an advantage in neurological development when compared to therapy to stop epileptic seizures.